Oxygen vacancy regulation in Nb-doped Bi2WO6 for enhanced visible light photocatalytic activity. Issue 39 (22nd July 2019) - Chen, Hao; Zhang, Changteng; Pang, Ya; Shen, Qianhong; Yu, Yang; Su, Yuxuan; Wang, Jiabang; Zhang, Fang; Yang, Hui
Abstract : Novel Nb-doped Bi2 WO6 nanosheets have been successfully synthesized by a simple hydrothermal method. Abstract : Novel Nb-doped Bi2 WO6 nanosheets have been successfully synthesized by a simple hydrothermal method. XRD, Raman spectra, XPS and SEM were adopted to analyze the structure and morphology of the samples, then the structure-dependent optical properties, photoelectric behavior and photocatalytic activities were investigated, and the structure–property relationship was also discussed. The results show that doping Nb 5+ can increase the oxygen vacancies in the Bi2 WO6 lattice and reduce the optical band gap of Bi2 WO6 . The oxygen vacancies also act as electron traps, which promote the separation of photogenerated carriers. Hence, compared with the pure Bi2 WO6, the as-prepared Nb-doped Bi2 WO6 nanosheets exhibit enhanced visible-light photocatalytic activity for removing contaminants in water such as rhodamine B and tetracycline.